Multiple compound odontomas in various regions of the maxilla: a rare case report - Moh Yusuf; Silvia Vera Indrawati (Odonto : Dental Journal, 2023)
Backgrounds: Odontomas often occur at a young age and are found incidentally in disturbed tooth eruptions, mostly intraosseous lesions. Compound odontomas have been identified as small tooth-like structures known as denticles. An accurate diagnosis of odontoma cannot be made on clinical examination. The majority of odontoma diagnoses have been made by radiographic examination. Odontoma often occurs unilaterally in one area with a single or multiple numbers, in this case, several areas have been found in the maxilla. The purpose of this case report is the radiographic evaluation of compound odontomas using panoramic radiographs and 3D Cone Beam CT. Case reports: A 12 years old female patient with her mother came to the orthodontist with the main complaint of crowding teeth and wanted treatment. On examination, an inflammation appeared on the palate behind the left RA lateral incisor. There was no history of trauma to the orofacial area. There was no family history of unerupted teeth or hypodontia and nothing relevant medical history. The orthodontist referred the patient for a panoramic radiograph and CBCT examination. Results: The results of the panoramic radiograph examination have showed radiopaque images resembling denticles in several regions, was made the case has been interesting to appoint in this case report, and this result was confirmed by the results of the CBCT examination which can show the location, number, and size of denticles in this patient.